The Bohob Collective’s Research on Catania: ‘exquisite corpse’ (diségno, 2023)
The paper investigates the research that the Bohob Architecture Collective is conducting on the city of Catania through two parallel paths: the Drawing of the city and the Minimum projects, held together by the drawing of architecture as a crucial tool in the discipline of architecture.Sebastiano Ittar's 1832 Topographical Plan of the City of Catania depicts a city in which a new plan is undermined by the persistence of ancient fragments. This is the theoretical basis on which the Bohob collective's Drawing of the city is 'founded', with the aim of elaborating a plan in continuity with Ittar's idea, proposing a minimal but decisive advance.The Minimum projects arise from the need to build urban places near the archaeological areas in the centre of Catania, currently perceived as marginal. They consist of a 'family' of precious shrines elaborated through the triptych, a drawing method that simultaneously holds together three scales: the 1:200 plan, the scale of the city; the 1:50 plan, the scale of the building; the 1:10 section, the scale of the architectural construct.To the triptych, as a necessary appendix, is added the view, not so much the simulation of a future reality but the evocative representation of the idea behind the project: the city, archaeology and the minimal project on the threshold between the two.
Keywords: archaeology; city; project; Catania; drawing